Impact of the COVID-19 pandemic on mental health, sleep and quality of life of nursing students in the mandatory internship (Research, Society and Development, 2022)
The present work aims to evaluate the impact of the COVID-19 pandemic on the mental health, sleep and quality of life of nursing students undergoing the mandatory internship. This is an observational research, with a cross-sectional design. The sample consisted of 39 university students from the 9th and 10th semester, of both genders in the Nursing course. Data were collected through a questionnaire developed by the researchers, which had 20 questions. Frequency and descriptive analysis of the variables age, gender, marital status, sleep quality analysis and psycho-emotional impacts were performed to better characterize the sample. 64.1% of the students belonged to the ninth semester, 82.1% were female, and 84.6% of the sample surveyed said they considered themselves an anxious person. It was also observed that 48.7% of respondents said they were not satisfied with the quality of their sleep. For 87.2% of respondents, the mandatory internship was responsible, at some point, for anxious symptoms. It is concluded that nursing students who were in mandatory internship in the midst of the COVID 19 pandemic, more than ever, find themselves in stressful situations, which leads to a greater overload of worry, work, anxiety and depression in the face of so many deaths, long work shifts and fear of infection.